Biometric Analysis Of Yield And Other Attributes In Coleus - Prakesh KM (Department of Plant Breeding and Genetics, College of Horticulture, 1996)
Studies were undertaken with thirty genotypes of coleus in the Department of Plant Breeding and Genetics, College of Horticulture, Vellanikkara during 1995-96 to estimate the extent of genetic variability, association among the selected characters and its partition into direct and indirect effects through path coefficient analysis under open as well as shaded conditions. The results have shown that the differences between the types were highly significant for most of the characters in the open condition and for all the characters in shaded condition. Low heritability and low genetic advance were shown for most of the economically important tuber characters in the open while the heritability and genetic advance were much greater in the shaded for the economically important characters. Expected genetic advance has shown that by selecting five per cent superior plants from available population, tuber yield could be increased by 52 g per plant in the shaded condition. Correlation studies have indicated that shoot characters like shoot length, number of leaves per plant and leaf area per plant and tuber characteristics like number of tubers per plant, tuber girth and tuber length are highly correlated with yield under open condition. However under shaded condition all the shoot characters are negatively correlated and all the tuber characters like number, length, girth and individual weight are to be given emphasis for identifying a high yielding genotype because of their high positive genotypic correlation with tuber yield. Path analysis projects that greater emphasis has to be laid for improving girth of tuber, number of tubers per plant individual tuber weight and tuber length in the open condition in selection while number of tubers, individual tuber weight and tuber girth should be given emphasis when selection is done for tuber yield in shade grown coleus.